(untitled) (Research, Society and Development, 2021)
The implementation of the capitalist modernization project in the Brazilian Amazon from 1964 intensified the process of occupation of this territory, resulting in its reconfiguration and emergence of conflicts associated with the struggle for land. This article aims to analyse how the different forms of use and occupation of the territory in Rural Settlements and the Extractive Reserves affect the environmental dynamics in the Brazilian Amazon. It attempted to articulate conceptual elements associated with the Territorial Planning with the empirical dimension originated from models and forms of appropriation of the territory conducted by the state. It was found that the patterns of use and occupation of these territories impact in different ways the Amazon Biome, and the Extractive reserves are presented as a model of territorial organization that is in tune with the environmental and socio-cultural singularities of the Amazon, by their nature, contribute to forest conversion in other uses, such as agriculture and livestock.